EP248 VALHUDES: a protocol for VALidation of HUman papillomavirus assays and collection DEvices for HPV testing on Self-samples and urine samples. (1st November 2019) - Arbyn, M; Peeters, E; Donders, G; De Sutter, P; Tjalma, W; Weyers, S; Vorsters, A; Van Keer, S; Benoy, I; Vanden Broeck, D; Bogers, J-P; Cocuzza, C; et al.
Abstract : Introduction/Background: Systematic reviews have concluded that hrHPV DNA testing using target-amplification tests is as accurate on vaginal self-samples as on clinician-taken specimens for the detection of cervical precancer. However, insufficient evidence is available for specific HPV assay/self-sample device combinations. Methodology: The VALHUDES protocol is designed as a diagnostic test accuracy study that aims to compare the clinical sensitivity and specificity of particular hrHPV assay(s) on vaginal self-samples and first-void-urine, collected in agreement with standardized protocols, with hrHPV testing on matched clinician-taken samples. Five hundred enrolled women referred to a colposcopy clinic are invited to collect a first-void urine sample and one or more vaginal self-samples with particular devices before collection of a cervical sample by a clinician. Sample sets are subsequently analysed in a laboratory accredited for HPV testing. Disease verification for all enrolled patients is provided by colposcopy combined with histological assessment of biopsies. Results: A first VALHUDES study has started in Belgium in December 2017 with enrolment from four colposcopy centres. The following assays are foreseen to be evaluated: RealTi m e High Risk HPV assay (Abbott), cobas-4800 and -6800 (Roche), Onclarity (BD), Xpert HPV (Cepheid) and Anyplex II HPV HR (Seegene). Conclusion: Given empirical evidence that the relative accuracy of HPV-testing on self- vs clinician-samples is robust across clinical settings, the VALHUDES protocol offers a framework for validation of HPV assay/self-sample device combinations that can be translated to a primary screening setting. Disclosure: A. Vorsters is co-founder and board member of Novosanis NV a spin-off of the University of Antwerp. M. Arbyn, E. Peeters, and M. Poljak are supported by the COHEAHR Network funded by the 7th Framework Programme of DG Research and Innovation, European Commission, Brussels, Belgium (grant No. 603019). M. Arbyn, E. Peeters, K. Cuschieri M. Poljak, and C. Cocuzza are supported by the SME Instrument Grant GA 80551, funded by the Horizon 2020 programme of DG Research and Innovation, European Commission, Brussels, Belgium. I. Benoy, D. Vanden Broeck and J. Bogers are employed by AML, a commercial lab performing cervical cytology and HPV testing.